Penerapan Evidance Based Practice Therapy Music White Noise terhadap Gangguan Tidur pada Pasien Stroke - Haryanti, Noviana; Agung, Rizki Nugraha; Yunitri, Ninik; Rayasari, Fitrian; Sulistyorini, Cahyo Ismawati (Universitas Malahayati, 2024)
ABSTRACT Stroke is a multi-complex neurological deficit disease that impacts not only the physical condition but also the psychological and social condition of stroke patients which can affect all aspects of their life. Sleep disorders are a group of conditions characterized by disturbances in the quality and quantity of a person's sleep. Sleep quality is related to sleep interruption due to frequent and repeated brief periods of nighttime wakefulness while sleep quantity is related to difficulty in initiating and maintaining sleep. This Evidance Based Nursing application aims to get an idea of the effect of white noise on sleep disorders in hospitalized stroke patients. This research is cross-sectional. The number of samples determined by the researcher, using the G*Power 3.1 application, obtained results of 5 people with 1 additional person as a respondent in preparation for the drop out of 1 person with a final total of 7 people. White noise music therapy was effective in reducing sleep disturbances in stroke patients before the intervention, the average sleep disturbance was 8.57, decreased to 4.14 after the intervention, with a significant effect of -3.91 and a p-value <0.001, even though the EBNP journal recommended therapy using Fitbit, in the field, the use of Fitbit is not recommended because it can interfere with the patient's sleep comfort with the device worn on the wrist throughout sleep. Keywords: Evidance Based Practice, White Noise Music Therapy, Sleep Disorders, Stroke Patients. ABSTRAK Stroke merupakan penyakit defisit neurologis multi kompleks yang berdampak bukan hanya pada kondisi fisik namun juga psikologis dan sosial pasien stroke yang dapat mempengaruhi semua sendi kehidupannya. Gangguan tidur merupakan suatu kumpulan kondisi yang dicirikan dengan adanya gangguan dalam kualitas dan kuantitas tidur seseorang. Kualitas tidur terkait dengan terputusnya tidur akibat periode singkat terjaga di malam hari yang sering dan berulang sedangkan kuantitas tidur terkait dengan kesulitan untuk memulai dan mempertahankan tidur. Aplikasi Evidance Based Nursing ini bertujuan untuk mendapatkan gambaran pengaruh white noise terhadap gangguan tidur pasien stroke yang menjalani rawat inap. Penelitian ini bersifat potong lintang (cross-sectional). Jumlah sampel yang ditentukan oleh peneliti, menggunakan aplikasi G*Power 3.1 dengan mendapatkan hasil 5 orang dengan 1 orang tambahan sebagai responden sebagai persiapan droop out 1 orang dengan total akhir 7 orang. Terapi musik white noise efektif dalam mengurangi gangguan tidur pasien stroke sebelum intervensi, rata-rata gangguan tidur adalah 8.57, turun menjadi 4.14 setelah intervensi, dengan efek signifikan sebesar -3.91 dan nilai p-value <0.001, meskipun jurnal EBNP merekomendasikan terapi menggunakan Fitbit, di lapangan, penggunaan Fitbit tidak disarankan karena dapat mengganggu kenyamanan tidur pasien dengan perangkat terpasang di pergelangan tangan sepanjang tidur. Kata Kunci: Evidance Based Practice Therapy Music White Noise, Gangguan Tidur, Pasien Stroke.